THE RELATIONSHIP BETWEEN THE APPLICATION OF NURSE THERAPEUTIC COMMUNICATION AND PATIENT SATISFACTION UNDERGOING HEMODIALYSIS THERAPY AT RAWALUMBU BEKASI HOSPITAL IN 2023 - Pangestika, Fitria Mega; Peraten Pelawi , Arabta Malem; Hidayati Bunga, Dinda Nur Fajri (Jurnal Medicare, 2023)
The achievement of patient satisfaction is inseparable from the communication applied by nurses. Conditions of dissatisfaction can have an impact on the quality of services provided by health workers, namely nurses. By properly implementing nurse therapeutic communication, it can improve the image of the profession and the image of the hospital. However, in reality the perception of patients undergoing hemodialysis therapy is still found to be unsatisfied patient satisfaction. This study aims to determine the relationship between the application of nurse therapeutic communication and patient satisfaction undergoing hemodialysis therapy at Rawalumbu Bekasi Hospital in 2023. The research method used is observational quantitative analytic with a cross sectional approach and purposive sampling technique based on inclusion criteria and obtained a sample size of 52 respondent. The results showed that with a significant level of 95% or an α value of 5% (0.05) the results of the Chi Square test obtained a p-value (0.000) <α value (0.05). This shows that H0 is rejected. The conclusion of the study is that there is a relationship between the application of nurse therapeutic communication and patient satisfaction undergoing hemodialysis therapy at Rawalumbu Bekasi Hospital in 2023.